Cross Level Analysis: The Role of Knowledge Management Mediates the Effect of Organizational Culture on Job Performance - Islamy, Fahmi Jahidah; Yuniarsih, Tjutju; Ahman, Eeng; Kusnendi, Kusnendi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2020)
This study aims to examine the influence of organizational culture on performance through knowledge management. The sample in this study amounted to 259 lecturers at private universities in the city of Bandung. Two-level hierarchical linear modeling (HLM) is used to analyze hierarchical structure data in this study, namely at the lecturer level as an individual and at the study program as a group level. The results showed that organizational culture had a significant positive effect on knowledge management, knowledge management had a significant positive impact on performance, and organizational culture had a positive and significant impact on performance directly or indirectly.